Dreams and reoccurrence of feelings. - Ruyneau de Saint George, Pierre (International Journal of Dream Research, 2016)
This note presents the hypothesis that dreams strictly echo feelings the dreamer experienced in recent life. This innovative translating approach has been tested on a series of 42 dreams including 344 scenes and 516 feelings. We show here that for 67 % of these dreams, the correlation with the past real-life is a very certain one. As none of the other dreams contradict this approach, we really can hypothesis that there is a link between the dreamt-feelings and the near-past real-life feelings.